Techniques to Improve Students' Skills in Speaking English Fluently - Utayeva Iroda Baxodirovna (Genius Journals, 2022)
there is no single typology of exercises for speaking skills. It is usually cited in didactic and methodological manuals as communicative exercises. The overall structure or division is difficult because the requirements for teachers and students are different. The typology of physical exercises can be created according to skill levels, for example. Then we have tasks and exercises for changing, different and finally free speech. If speech is caused by the division of speech into dialogical and mono-logical speech, the results of the typology of exercises that provide tasks and exercises for the development of monological and dialogical speech are considered. In this article, feedback and feedback will be made on how to improve the speaking skills of student youth in English.
Keywords: speaking skill; advanced vocabularies; active language; speaking partner